2016
DOI: 10.4103/0971-9784.179631
|View full text |Cite
|
Sign up to set email alerts
|

Warden repair for superior sinus venosus atrial septal defect and anomalous pulmonary venous drainage in children: Anesthesia and transesophageal echocardiography perspectives

Abstract: Objective:Review of intraoperative anesthetic challenges and the role of transesophageal echocardiography in children with sinus venosus atrial septal defect and partial anomalous pulmonary venous drainage undergoing Warden repair.Design:A retrospective observational case series.Methodolgy:Pediatric patients who underwent Warden repair between October 2011-September 2015 were recruited. Their preoperative clinical details, anesthetic techniques, intraoperative TEE findings and postoperative events were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, there are associated low risks of sinus node dysfunction, atrial arrhythmias, and pulmonary or systemic venous occlusion after surgery. [33][34][35][36][37][38][39][40][41][42][43][44] This study aimed to review the prevalence of complex sinus venosus defects defined as either the presence of multiple anomalous pulmonary venous sites or high insertion of the anomalous pulmonary vein into the superior caval vein, ascertain the imaging modalities employed in delineating the anatomical variants, and the surgical outcome in this cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are associated low risks of sinus node dysfunction, atrial arrhythmias, and pulmonary or systemic venous occlusion after surgery. [33][34][35][36][37][38][39][40][41][42][43][44] This study aimed to review the prevalence of complex sinus venosus defects defined as either the presence of multiple anomalous pulmonary venous sites or high insertion of the anomalous pulmonary vein into the superior caval vein, ascertain the imaging modalities employed in delineating the anatomical variants, and the surgical outcome in this cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that, surgery is not free from significant complications, specially arrhythmias, due to sinus node lesion, obstruction of SVC-AD junction and, mainly, pulmonary vein obstruction. 7,9,16,17 Sinus venosus atrial septal defect transcatheter occlusion was first reported by Meier et al and Garg et al in 2014. 8,18,19 Meier managed to implant a regular nitinol ASD device and plugged the RUPV.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of stenosis at the Warden anastomosis was defined by Doppler gradients across the cavoatrial junction of >5 mmHg or loss of biphasic pattern in the superior caval vein. 5,6 Patients were followed up in the outpatient clinic through clinical examination, transthoracic echocardiography, and Holter monitoring (when needed) at 3 and 6 months post-operatively and then at regular intervals of 1 year. Post-operative sinus node dysfunction was defined as persistent sinus bradycardia (<50 beats/ minutes), pauses of more than 3 seconds, or persistent nodal rhythm > 1 week, especially with the need for permanent pacemaker.…”
Section: Methodsmentioning
confidence: 99%